ANALISIS BIBLIOMETRIK PENERAPAN PRINSIP SYARIAH PADA PSAK 108 (ASURANSI SYARIAH) MENGGUNAKAN VOSVIEWER - Ade Purnama, Eftry; Inda Fadhila Rahma, Tri; Nurwani (ITB AAS Indonesia Surakarta, 2025)
This study aims to identify research trends, keyword occurrences, and author collaborations related to the application of sharia principles in PSAK 108 to Islamic insurance during the 2019–2024 period using a bibliometric approach. This study is the first bibliometric analysis related to PSAK 108 using VOSviewer, presenting a visual mapping of thematic networks and collaborations. Data were collected through Google Scholar, analyzed using Publish or Perish (version 8), and visualized with VOSviewer (version 1.6.19). This study used a bibliometric review method with keyword-based searches and co-occurrence mapping, producing output in CSV and RIS formats. A total of 323 articles were analyzed. The results show a peak in publications in 2023, six keyword clusters were found, and author collaborations are still limited. Dominant keywords include